2004
DOI: 10.1080/10790268.2004.11753740
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use Associated With Cervical Spinal Cord Injury

Abstract: Objectives: To determine whether akohol use at time of spinal cord injury (SCI) is more common with cervical injury than with lower levels of spinal injury.Methods: Veterans and nonveterans with SCI were assessed at a Veteran's Affairs Medical Center from 1994 through 2002 and completed a health questionnaire that included information on alcohol use at time of traumatic injury.Results: Of 362 men. 45% had neurologically complete or incomplete cervical injuries. Participants with cervical injury were more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
(25 reference statements)
0
19
2
1
Order By: Relevance
“…Similarly, Garrison et al . found that among 362 male patients with spinal cord injuries, those with cervical injuries were twice as likely as those without cervical injury to have been using alcohol when injured [10].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Garrison et al . found that among 362 male patients with spinal cord injuries, those with cervical injuries were twice as likely as those without cervical injury to have been using alcohol when injured [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a questionnaire‐based study, Garrison et al . found a significantly greater frequency of self‐reported alcohol use at the time of injury amongst individuals with cervical SCI compared with individuals with SCI at a more caudal spine level. Nonetheless, Heinemann et al .…”
Section: Discussionmentioning
confidence: 91%
“…For instance, one could speculate that only individuals involved in driving accidents were tested for BAC, and those who had been drinking were more likely to behave recklessly increasing the chance of being involved in graver car accidents with worse injuries. In a questionnaire-based study, Garrison et al [22] found a significantly greater frequency of self-reported alcohol use at the time of injury amongst individuals with cervical SCI compared with individuals with SCI at a more caudal spine level. Nonetheless, Heinemann et al [23] have documented false-negative self-reports of alcohol intoxication in 41% and false-positive self-reports in 18% compared with BAC.…”
Section: Blood Alcohol Concentration and Injury Characteristicsmentioning
confidence: 99%
“…In contrast to studies focusing on causes and context of injury occurrence, fewer efforts have been employed to compare the association of acute alcohol consumption with different types of injury. The role of acute consumption among trauma patients has been reported for different body regions and a variety of injury natures [127][128][129][130][131][132][133][134][135][136] . Marked variations seem to exist in terms of alcohol involvement across types of injury (e.g.…”
Section: Alcohol and Type Of Injurymentioning
confidence: 99%